On the equivalent descriptions of family of functional dependencies in the relational data model - Thi, Vũ Đức (Journal of Computer Science and Cybernetics, 2016)
The family of functional dependencies (FDs) was introduced by E.F. Codd. Equivalent descriptions of family of FDs play essential rules in the design and implementation of the relation datamodel. It is known [1,3,4,5,7,8,12,13,15] that closure operations, meet-semilattices, families of members which are not intersections of two other members give the equivalent descriptions of family of FDs. i.e. they and family of  FDs determine each other uniquely. These equivalent description were  successfully applied to find many desirable properties of  functional dependency. This paper introduces the concept of maximal family of attributes. We prove that this family is an equivalent description of family of FDs. The concept of nonredundant family of attributes is also introduced in this paper. We present some characterizations and desirable properties of these families.